2018
DOI: 10.1101/gad.316059.118
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Mdm2 and Mdm4 alternative splicing underlies motor neuron death in spinal muscular atrophy

Abstract: Ubiquitous deficiency in the survival motor neuron (SMN) protein causes death of motor neurons-a hallmark of the neurodegenerative disease spinal muscular atrophy (SMA)-through poorly understood mechanisms. Here, we show that the function of SMN in the assembly of spliceosomal small nuclear ribonucleoproteins (snRNPs) regulates alternative splicing of Mdm2 and Mdm4, two nonredundant repressors of p53. Decreased inclusion of critical Mdm2 and Mdm4 exons is most prominent in SMA motor neurons and correlates with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
132
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(165 citation statements)
references
References 55 publications
(126 reference statements)
31
132
2
Order By: Relevance
“…We also showed that selectivity is established through the convergence of distinct mechanisms of p53 regulation including stabilization and phosphorylation of its N-terminal transcription-activation domain (TAD) , which only occur in the pool of vulnerable SMA motor neurons destined to die. Recently, we demonstrated that p53 upregulation results from dysregulated alternative splicing of Mdm2 and Mdm4 -the two main inhibitors of p53's stability and function (Toledo and Wahl, 2006;Vousden and Prives, 2009) -due to reduced snRNP levels in SMA motor neurons (Van Alstyne et al, 2018a), thereby directly linking neurodegeneration to specific splicing changes induced by SMN deficiency. However, the converging mechanism(s) responsible for selective phosphorylation of the TAD of p53 required for degeneration of SMA motor neurons is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…We also showed that selectivity is established through the convergence of distinct mechanisms of p53 regulation including stabilization and phosphorylation of its N-terminal transcription-activation domain (TAD) , which only occur in the pool of vulnerable SMA motor neurons destined to die. Recently, we demonstrated that p53 upregulation results from dysregulated alternative splicing of Mdm2 and Mdm4 -the two main inhibitors of p53's stability and function (Toledo and Wahl, 2006;Vousden and Prives, 2009) -due to reduced snRNP levels in SMA motor neurons (Van Alstyne et al, 2018a), thereby directly linking neurodegeneration to specific splicing changes induced by SMN deficiency. However, the converging mechanism(s) responsible for selective phosphorylation of the TAD of p53 required for degeneration of SMA motor neurons is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…p53 depletion rescues mdm2 mutant phenotypes (27). Abnormal mdm2 splicing and p53 activation are associated with the death of motor neurons in SMA (28). We found inhibition of the p53/Mdm2 pathway brought no alteration to survival or regeneration in the gemin5 mutants (Suppl.…”
Section: Discussionmentioning
confidence: 66%
“…9A). Several lines of published evidence indicate that p53 interacts with Mdm2 and activation of the p53/Mdm2 pathway is associated with SMN complex activity and SMA (27)(28)(29). To investigate a potential role for the tp53/Mdm2 pathway in hair cell regeneration, we depleted tp53 genetically in both the smn1 and gemin5 mutant backgrounds.…”
Section: Observed Upregulation Of the Tp53/mdm2 Pathway Was Not The Mmentioning
confidence: 99%
“…A second study suggests that the underlying mechanism of motor neuron death in SMA is related to p53 signaling, specifically altered splicing of two p53 repressors, Mdm2 and Mdm4 (Van Alstyne et al, ). Using an SMA mouse model, the authors demonstrate that SMN deficiency selectively promotes exon skipping of two major spliceosome regulated exons, Mdm2 Exon 3 and Mdm4 Exon 7.…”
Section: Spinal Muscular Atrophymentioning
confidence: 99%